2017
DOI: 10.1155/2017/4624062
|View full text |Cite
|
Sign up to set email alerts
|

Buzzing Wild Bee Visits Enhance Seed Set in Eggplant, Solanum melongena

Abstract: Sixty percent of the angiosperms with poricidal anthers are buzz-pollinated by bees (Hymenoptera: Apoidea: Apiformes). Plant taxa with Solanum-type flowers have larger anthers and shorter filaments. Solanum melongena (Solanaceae) is more commonly and efficiently pollinated by buzz pollinators. The present study documented bees and their diurnal pattern of visitation to flowers, relationship between their handling time and flower age, and the effect of bee visits on fruit and seed set in S. melongena in two sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We found that long tongued bees like Eucera, Anthophora, and Amegilla were more abundant at Fabaceae flowers that are characterized by flowers with a deep corolla tube (Aouar-sadli et al, 2008;Shebl and Farag, 2015;Marzinzig et al, 2018). Likewise, Solanaceae crops that typically require buzz pollination for fertilization were found to be visited mostly by X. pubescens and A. quadrifaciata, the two species which represent groups of efficient buzz pollinators (Gemmill-herren and Ochieng, 2008;Jayasinghe et al, 2017;Toni et al, 2020;Udayakumar et al, 2021).…”
Section: Wild Bees Visiting Crops In Moroccomentioning
confidence: 96%
See 1 more Smart Citation
“…We found that long tongued bees like Eucera, Anthophora, and Amegilla were more abundant at Fabaceae flowers that are characterized by flowers with a deep corolla tube (Aouar-sadli et al, 2008;Shebl and Farag, 2015;Marzinzig et al, 2018). Likewise, Solanaceae crops that typically require buzz pollination for fertilization were found to be visited mostly by X. pubescens and A. quadrifaciata, the two species which represent groups of efficient buzz pollinators (Gemmill-herren and Ochieng, 2008;Jayasinghe et al, 2017;Toni et al, 2020;Udayakumar et al, 2021).…”
Section: Wild Bees Visiting Crops In Moroccomentioning
confidence: 96%
“…A recent study comparing the effect of reduction of fertilizer input, irrigation, and pollination, found that a reduction of insect pollination has a stronger effect on crop yield than other agricultural inputs (Fijen et al, 2020). Furthermore, insect pollination enhances the yield and the quality of many crops at both the local and global scale, such as for faba bean (Aouarsadli et al, 2008;Cunningham and Le Feuvre, 2013), strawberries (Abrol et al, 2019;MacInnis and Forrest, 2019), apple (Garratt et al, 2014a;Hünicken et al, 2021), eggplant (Jayasinghe et al, 2017), cucumber (Christmann et al, 2017(Christmann et al, , 2022, and tomato (Bashir et al, 2018;Toni et al, 2020). Moreover, many countries are becoming increasingly dependent on pollinators because production has shifted to more pollinator-dependent crops (Aizen et al, 2008;Potts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also checked fruit sets 15 days after pollination, by observing pollen tube growth in pistils and estimating pollination quality through the percentage of ovules penetrated by pollen tubes. In another study, the total number of fruits and seeds and eggplant weight and length were indirect measures of the success of wild bee visits [68]. These authors also investigated the relationship between handling time in flowers of different ages (newly open, 1 day old, 2 days old, more than 2 days old) and the number of pollen grains remaining on the anther.…”
Section: Pollination Successmentioning
confidence: 99%
“…All have been widely used in recent decades. Walking transect ranges span from 100 × 1 m trails to be covered in 20 min [68], to 200 × 1 m in 20 min [76], and 250 × 4 m in 50 min [59]. Walking transects are usually defined as variable [31,76,77] when the position and direction of a transect are chosen randomly during the sampling, or standard-fixed when the same spot is visited in subsequent monitoring periods.…”
Section: Capturementioning
confidence: 99%
“…melongena Linnaeus, 1753), is a major crop in many countries whose pollination requirements remain poorly studied [ 26 , 27 ]. Eggplant flowers are hermaphroditic and, can be self-compatible [ 27 ], though heavier fruit and larger number of seeds can result from cross pollination by sonicating bees [ 28 , 29 ]. Mexico is a center of diversification of the genus Solanum and the country is one of the largest producers of Solanum crops in the Americas, including eggplant, with ca.…”
Section: Introductionmentioning
confidence: 99%